+0  
 
0
204
1
avatar

What is the intermediate step in the form (x+a)^2=b(x+a)2=b as a result of completing the square for the following equation?

 

2x^2+42x+260=6x

 

You answer should look like this:

(___)^2=__

 Feb 10, 2021
 #1
avatar+120127 
+1

2x^2 + 42x  +  260   =  6x

 

2x^2  + 42x  -  6x  +  260  =   0

 

2x^2   +  36x  +  260  =  0                divide  through  by  2

 

x^2 +  18x  +  130  =   0            

 

take 1/2 of 18  = 9,,,,square it  = 81....add it and subtract it

 

x^2  +  18x  +  81  +  130  -  81  =   0       factor   the first three terms, simplify the rest

 

(x  + 9)^2  +  51  =  0 

 

(x + 9)^2   =   -51

 

 

cool cool cool

 Feb 10, 2021

25 Online Users

avatar
avatar
avatar
avatar
avatar